Missense variants in the TRPM7 α-kinase domain are associated with recurrent pediatric acute liver failure - Schlieben, Lea D.; Achleitner, Melanie T.; Bourke, Billy; Diesner, Max; Feichtinger, René G.; Fichtner, Alexander; Flechtenmacher, Christa; Hadzic, Nedim; Hegarty, Robert; Heilos, Andreas; Janecke, Andreas; Konstantopoulou, Vassiliki; et al. (Hepatology communications, 2024)
Background: - Pediatric acute liver failure (PALF) is a rare and life-threatening condition. In up to 50% of PALF cases, the underlying etiology remains unknown during routine clinical testing. This lack of knowledge complicates clinical management and liver transplantation decisions. Recently, whole-exome sequencing has identified genetic disorders in a large number of cases without specific laboratory biomarkers or metabolic fingerprints. - Methods: - We describe how further analysis of whole-exome sequencing data combined with proteomic analyses in 5 previously unsolved PALF patients, where no pathogenic variants in genes previously associated with acute liver failure were identified, revealed rare biallelic variants in transient receptor potential cation channel subfamily M member 7 (TRPM7). - Results: - We establishe TRPM7 as a novel disease gene for PALF. Yet, the cation channel kinase TRPM7 has not been associated with any Mendelian disorder. No homozygous loss-of-function variants were found in in-house exomes or publicly available databases. Rare biallelic TRPM7-variants were significantly enriched in the PALF cohort compared with a pediatric control cohort. Viral infections preceded the majority of PALF episodes. Recurrent PALF episodes characterized the disease course with rapid progression, leading to early death in 3 cases. Proteomic analyses of patient fibroblasts unveiled significantly reduced TRPM7 protein levels, indicative of functional impairment. Severely reduced Mg2+ levels in one individual with a mutation in the channel domain suggests a potential interaction between disturbed Mg2+ homeostasis and PALF. The consistent presence of mutations in the TRPM7 protein-kinase-domain across all patients suggests its specific relevance in PALF. - Conclusions: - Our data extend the genetic spectrum of recurrent PALF and prompt consideration of TRPM7 in children with unexplained liver failure.
Gesehen am 25.07.2025